Boronate-dextran: an acid-responsive biodegradable polymer for drug delivery - Li, Linxian; Bai, Zewei; Levkin, Pavel (Biomaterials, 2013)
Stimuli-responsive drug carriers have great potential to deliver bioactive materials on demand and to a specific location within the human body. Acid-responsive drug carriers can specifically release their payload in the acidic microenvironments of tumors or in the endosomal or lysosomal compartments within a cell. Here we describe an approach to functionalize vicinal diols of dextran with hydrophobic boronate esters in order to produce a water insoluble boronate dextran polymer (B-Dex), which spontaneously forms acid-responsive nanoparticles in water. We show the encapsulation of a hydrophobic anticancer drug doxorubicin into the particles. Hydrolysis of the boronate esters under mild acidic conditions recovers the hydrophilic hydroxyl groups of the dextran and disrupts the particles into water soluble fragments thereby leading to a pH-responsive release of the drug. According to dynamic light scattering (DLS) and UV/Vis spectroscopy, mild acidic conditions (pH 5.0) lead to a three-fold increase in the degradation of the particles and a four-fold increase in the release of the drug compared to the behavior of particles at pH 7.4. In vitro tests in Hela cells show no toxicity of the empty B-Dex nanoparticles, while the toxicity of doxorubicin-loaded B-Dex nanoparticles is comparable to that of the doxorubicin·HCl drug. Confocal fluorescence microscopy reveals that 100% of the Hela cells uptake doxorubicin-loaded B-Dex nanoparticles with a preferential accumulation of the nanoparticles in the cytoplasm.